The Sovereignty of the Crown Dependencies and the British Overseas Territories in the Brexit Era - Maria Mut Bosque (Island Studies Journal, 2020)
This paper focuses on an analysis of the sovereignty of two territorial entities that have unique relations with the United Kingdom: the Crown Dependencies and the British Overseas Territories (BOTs). Each of these entities includes very different territories, with different legal statuses and varying forms of self-administration and constitutional linkages with the UK. However, they also share similarities and challenges that enable an analysis of these territories as a complete set. The incomplete sovereignty of the Crown Dependencies and BOTs has entailed that all these territories (except Gibraltar) have not been allowed to participate in the 2016 Brexit referendum or in the withdrawal negotiations with the EU. Moreover, it is reasonable to assume that Brexit is not an exceptional situation. In the future there will be more and more relevant international issues for these territories which will remain outside of their direct control, but will have a direct impact on them. Thus, if no adjustments are made to their statuses, these territories will have to keep trusting that the UK will be able to represent their interests at the same level as its own interests.